Efficacy of corticosteroid injection in rock climber's tenosynovitis - Schöffl, Volker Rainer; Strohm, P.; Lutter, C. (Hand Surgery and Rehabilitation, 2019)
While many finger conditions in climbers have been studied extensively, no data exist on the treatment of rock climber's finger flexor tenosynovitis. The purpose of this study was to evaluate the outcomes after corticosteroid injection. The study included rock climbing athletes suffering from chronic (longer than 6 weeks) finger flexor tenosynovitis who were seen at our clinic in 2017. All 42 patients received two corticosteroid injections within a 7–10 day period. Thirty-one climbers (73.8%) were pain free after the second injection and a mean of 20.9 ± 23.1 days. The climbers reported an 84.2% decrease in pain level and no complications. The positive outcome after corticosteroid injection therapy and the absence of complications justifies this invasive approach in rock climbing athletes.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Finger injury; Flexor tendon; Overuse; Tenosynovitis